Stunting Prevention Through at Home Dental Care for Children: A Review - Zakki, Muhamad; Delima, Anita Rosa; Riyadi, Nugroho Ahmad (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Dental and oral health is a healthy condition of hard tissue and soft tissue, and stunting is a problem of malnutrition, which is quite high in Indonesia, namely 37.2% in 2013 and 30.8% in 2018. Objective: This article aims to create a guide for parents of toddlers on how to maintain children's dental health at home, with the hope of contributing to reducing the prevalence of Early Childhood Caries and stunting in toddlers in Indonesia. Methods: The library sources for this article were obtained from several valid literature based on the author's expertise and compiled with theory or research from several journals published by Elsevier, Oxford University Press, Blackwell Munksgaard, Google Scholar, and Pubmed. Results: Nutritional problems are caused by several factors, both directly and indirectly, which are interrelated. Nutrition and oral health have a reciprocal relationship that influences each other. Proper nutrition is needed to maintain healthy teeth and mouth and healthy teeth and mouth to get adequate nutritional intake. Conclusion: Parents, especially mothers, play a key role in maintaining children's dental health and preventing stunting because toddlers cannot yet effectively clean their teeth.